2016
DOI: 10.1177/1050651916636373
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Rhetorical Norms and Electronic Eloquence

Abstract: Advances in digital media have made an impact on traditional rhetorical culture, thus shifting expectations and norms associated with orality and public presentation. Technology, entertainment, and design (TED) talks represent a new genre of presentation characteristic of Jamieson’s notion of electronic eloquence in that presenters weave together an engaging narrative complete with a strong visual presence. This study applies Bandura’s social cognitive learning theory to explore how students make sense of TED … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…The vocabulary obtained also increased while students watched the video. Also their courage to speak in public also proved positive (Kedrowicz & Taylor, 2016). In short, TED Talks works successfully in motivating students both in language learners and a better public speaker.…”
Section: Downloadmentioning
confidence: 83%
“…The vocabulary obtained also increased while students watched the video. Also their courage to speak in public also proved positive (Kedrowicz & Taylor, 2016). In short, TED Talks works successfully in motivating students both in language learners and a better public speaker.…”
Section: Downloadmentioning
confidence: 83%
“…Regarding scientific coverage, only few studies investigated TED talks. One study examined presentation characteristics of TED talks and concluded that they can be a valuable source for teaching and communicating ideas to students (Kedrowicz and Taylor 2016). Other scholars found that women gave fewer TED talks than men .…”
Section: Why Study Ted Talks?mentioning
confidence: 99%
“…Our rhetorical analysis of +POOL is not meant to be generalizable across all entrepreneurial ventures; rather, we situate crowdfunding as an exemplary model of civic entrepreneurship, one that foregrounds the deeply rhetorical work involved in developing and soliciting financial and social support for a hybrid solution. That is, like others (Bracken Scott, 2016; Dorpenyo, 2015; Kedrowicz & Taylor, 2016; Rice, 2016; Salvo, Pflugfelder, & Prenosil, 2010), we ground our discussion in +POOL as a rhetorical artifact, specifically examining how +POOL provides a generative way of understanding the role that rhetoric plays in the day-to-day work of civic entrepreneurship. Moreover, by bringing to light the vast array of rhetorical activities involved in +POOL, we further demonstrate the vital role that rhetoric and technical communication play in civic entrepreneurship—beyond that of delivering a persuasive pitch to investors or a proposal to stakeholders.…”
mentioning
confidence: 92%